The Concept of Gus Dur's Humanism in Nusantara Islam - M. Aris Munandar; Encung Heriyadi (MAQOLAT: Journal of Islamic Studies, 2024)
Gus Dur's concept of the indigenization of Islam is related to what is called Islam Nusantara, namely the embodiment of Islam through local traditions and culture of the archipelago. Thus rejecting local forms of Islam which are actually  manifestations  of  Islamic  universalism.  That  is,  actually  locality  is colored by Islam, not vice versa, Islam is colored by locality. So that at this point, the indigenization of Islam found its urgency as a method in forming the Islam of the Archipelago. The formulation of the problem of this research is; What is Gus Dur's concept of humanism in Islam Nusantara and what are Gus Dur's contributions to Islam Nusantara. This study uses library research (library research), which is a collection of data or materials related to the  theme of discussion and problems, which are taken from library sources and this type of research  uses qualitative  methods.  The  results of  this study indicate  that  the relevance of Gusdur's concept of humanism to the Islam of the archipelago is as follows: First, according to Gus Dur his views on Islam are undergoing major changes. Second, according to Gus Dur, religion must be able to change people's morality by being patient and nurturing each other so that it conforms to Islamic teachings which are believed to be true by providing a good example as the main vehicle in the formation of morality that applies in the midst of a very high pluralistic society. Gus Dur also emphasized the value of monotheism in the concept of maqashid al-shari'ah which is embodied in the concept of kulliyatul khams, namely the aim of sharia to protect basic human rights.